Maize (Zea mays L.) seedling leaf nuclear proteome and differentially expressed proteins between a hybrid and its parental lines. Issue 9 (May 2014) - Guo, Baojian; Chen, Yanhong; Li, Chuan; Wang, Tianya; Wang, Rui; Wang, Bo; Hu, Sha; Du, Xiaofen; Xing, Hongyan; Song, Xiao; Yao, Yingyin; Sun, Qixin; et al.
<x xml:space="preserve">Abstract</x> To better understand the underlying molecular basis of leaf development in maize, a reference map of nuclear proteins in basal region of seedling leaf was established using a combination of 2DE and MALDI‐TOF‐MS. In total, 441 reproducible protein spots in nuclear proteome of maize leaf basal region were detected with silver staining in a pH range of 3–10, among which 203 spots corresponding to 163 different proteins were identified. As expected, proteins implicated in RNA and protein‐associated functions were overrepresented in nuclear proteome. Remarkably, a high percentage (10%) of proteins was identified to be involved in cell division and growth. In addition, comparative nuclear proteomic analysis in leaf basal region of highly heterotic hybrid Mo17/B73 and its parental lines was also performed and 52 of 445 (11.69%) detected protein spots were differentially expressed between the hybrid and its parental lines, among which 16 protein spots displayed nonadditively expressed pattern. These results indicated that hybridization between two parental lines can cause changes in the expression of a variety of nuclear proteins, which may be responsible for the observed leaf size heterosis.